Does a healthy lifestyle reduce the risk of obesity in type 1 diabetes? - Michalski, Mateusz; Zozulińska-Ziółkiewicz, Dorota (Journal of Medical Science, 2025)
A healthy lifestyle is recommended for every person with type 1 diabetes. Unfortunately, the incidence of type 1 diabetes is steadily increasing. Many studies confirm that maintaining a balanced diet or incorporating physical activity helps to maintain good health over the long term. It helps to balance the diabetes metabolically and to prevent the development of excessive body weight. Making appropriate lifestyle modifications, as recommended by researchers and associations, will undoubtedly help with this. This study aims to analyse the impact of a healthy lifestyle, including a balanced diet, sleep hygiene, psychological conditions,  insulin therapy and physical activity, on metabolic control and the prevention of excess body weight in patients with type 1 diabetes. The introduction and alignment of the described components in patients with type 1 diabetes contribute to better metabolic control of the disease and reduce the risk of excessive body weight.